Beyond paradise. Season one [videorecording (DVD)] - Thorogood, Robert; Jordan, Tony, 1957- (BBC Studios, 2023)
It follows DI Humphrey Goodman and his fiancée Martha as they leave London to navigate a new life together on the beautiful Devon coast. Our heroes are thrown in at the deep end as Martha pursues her dream of running her own restaurant and Humphrey takes up the vacant position of Detective Inspector at Shipton Abbott police station, an outpost of the Devon & Cornwall Police district. Quickly making an impression on his somewhat eclectic team, Humphrey sets out to crack a host of baffling cases, but will his unusual methods win over his new colleagues?